1992
DOI: 10.1017/s0022112092000703
|View full text |Cite
|
Sign up to set email alerts
|

The response and symmetry properties of a cylinder wake subjected to localized surface excitation

Abstract: Symmetric and antisymmetric periodic disturbances introduced directly into the boundary layer on a circular cylinder at low Reynolds number are shown by experiment to be capable of modifying the vortex formation process and changing the vortex shedding frequency. Spectral measurements have shown that the antisymmetric vortex shedding mode is strongly coupled to the symmetric first harmonic mode. When symmetric excitation is applied, three different shapes of the mean velocity profiles can be identified as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 27 publications
3
36
0
1
Order By: Relevance
“…7 Recently, Cheng et al 8 investigated a novel perturbation technique using curved piezoceramic actuators embedded underneath the surface of a square cylinder to alter interactions between a flexibly supported cylinder and cross flow. Given a properly set perturbation frequency, both vortex shedding and vortex-induced vibration were significantly reduced as a result from actuator-generated surface perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, Cheng et al 8 investigated a novel perturbation technique using curved piezoceramic actuators embedded underneath the surface of a square cylinder to alter interactions between a flexibly supported cylinder and cross flow. Given a properly set perturbation frequency, both vortex shedding and vortex-induced vibration were significantly reduced as a result from actuator-generated surface perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Steady blowing effect, tangentially to the cylinder model through a slot has been investigated by Waka et al (1985) and illustrates the modification of the flow for various positions and shapes of the injector. The recent development of synthetic or pulsed jets (Amitay et al, 1997;Williams et al, 1992) on cylinder models has proved that such a new technique is a very efficient way to manipulate the flow. These types of unsteady pneumatic actuators have the characteristics of being possibly miniaturized, they do not produce any average mass addition to the near wake and they require very little energy.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of the synthetic jet for flow control is to manipulate the flow seperation around a circular cylinder. In most of the previous works, the jet exit was usually positioned near the separation point or inside the separation region [3][4][5][6] . Amitay et al [3] experimentally investigated the cylinder flow control with synthetic jets, which issued from a pair of slots with the jet exit angle α from 0° to 180°.…”
mentioning
confidence: 99%
“…They both found that the synthetic jets could efficaciously delay flow seperation and enable the seperation region to become much smaller and even completely disappearing, which led to a reduction in drag. Besides, Williams et al [6] also placed the jet exit orifice near the upstream of the separation point and they pointed out that the jet could substantially alter the mode of the near-wake vortex formation, including a limiting case where the formation of large-scale Karman vortices were controlled.…”
mentioning
confidence: 99%